Development and experimental validation of an integrated evaluation framework for EMS smartwear electrodes - Lee, G.; Chae, U.; Yun, J.; Seo, D.; Jang, I.; Ham, G.; Kim, T.; Kim, H. (Sensors, 2025)
This study presents an integrated evaluation framework for textile-based electrical muscle stimulation smartwear electrodes, combining physiological and user-centered assessments to ensure comprehensive performance analysis. Four electrode types—lock stitch, knit, hot stamping, and moss stitch—were examined using a systematic five-step process with nine participants. Quantitative measurements were obtained using electromyography to determine maximum voluntary contraction and tensiomyography to assess muscle contraction velocity. The knit electrode demonstrated a statistically significant reduction in maximum voluntary contraction following stimulation (W = 2.0, p = 0.012, Cohen`s d = 0.58), indicating effective neuromuscular activation and fatigue induction. The moss stitch electrode also showed a notable trend toward reduced muscle activation (W = 6.0, p = 0.055, d = 0.37). In contrast, the lock stitch and hot stamping electrodes exhibited negligible changes. User experience surveys revealed overall high acceptance across all electrode types (4.0-4.5 of mean scores on a 5-point scale), with the moss stitch electrode receiving the highest ratings for perceived safety and minimal skin discomfort, while the hot stamping electrode scored lowest in breathability. The proposed framework enables balanced evaluation of both functional performance and user experience, offering practical design guidance for optimizing textile electrodes across applications ranging from high-intensity athletic training to low-intensity rehabilitation.